2014
DOI: 10.1111/jog.12618
|View full text |Cite
|
Sign up to set email alerts
|

Lipid‐soluble fraction of Shakuyaku‐kanzo‐to inhibits myometrial contraction in pregnant women

Abstract: These results suggest that lipid-soluble substances with low polarity derived from kanzo are responsible for the inhibitory effect of shakuyaku-kanzo-to on myometrial contraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…The study found that the lipid-soluble fractions, obtained from shakuyaku-kanzo-to and kanzo, inhibited myometrial contraction, while the water-soluble fractions had no effect on contractions. These results suggest that lipid-soluble substances with low polarity derived from kanzo are responsible for the inhibitory effect of shakuyaku-kanzo-to on myometrial contraction 68…”
Section: Partus Preparatorsmentioning
confidence: 78%
See 1 more Smart Citation
“…The study found that the lipid-soluble fractions, obtained from shakuyaku-kanzo-to and kanzo, inhibited myometrial contraction, while the water-soluble fractions had no effect on contractions. These results suggest that lipid-soluble substances with low polarity derived from kanzo are responsible for the inhibitory effect of shakuyaku-kanzo-to on myometrial contraction 68…”
Section: Partus Preparatorsmentioning
confidence: 78%
“…These results suggest that lipid-soluble substances with low polarity derived from kanzo are responsible for the inhibitory effect of shakuyakukanzo-to on myometrial contraction. 68 Western Herbs for Labor Preparation Blue Cohosh (Caulophyllum thalictroides) Blue Cohosh was labeled in the United States Pharmacopeia in the 19th century for labor induction and is often used in combination with other herbs including black cohosh. 69 Blue cohosh contains n-methylcytisine and anagyrine, both of which have been associated with fetal malformations including cardiovascular and craniofacial anomalies.…”
Section: Tcm and Eastern Herbs For Contraction Inhibition And Painmentioning
confidence: 99%
“…SKT has been reported to inhibit acetylcholine‐induced and neurogenic contractions of the gastrointestinal tract and to decrease unfavorable smooth muscle contractions during upper and lower gastrointestinal endoscopy . SKT also inhibits oxytocin‐induced myometrial contractions of uterine tissue in pregnant women in a dose‐dependent manner . In addition to ameliorating muscle symptoms, SKT has been found to improve extrapyramidal symptoms while exerting no significant effect on psychiatric symptoms .…”
Section: Discussionmentioning
confidence: 99%